1993
DOI: 10.1161/01.atv.13.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hepatic lipase on LDL in normal men and those with coronary artery disease.

Abstract: Hepatic triglyceride lipase (HL) is thought to play a role in the formation of low density lipoproteins (LDLs) from small very low density lipoproteins (VLDLs) and intermediate density lipoproteins (IDLs).To analyze the possible physiological role of HL in determining LDL buoyancy, size, and chemical composition, HL activity and LDL were studied in 21 patients with coronary artery disease (CAD) and 23 normolipidemic subjects. In both groups, LDL buoyancy and size were inversely associated with HL activity leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
118
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(132 citation statements)
references
References 34 publications
13
118
1
Order By: Relevance
“…Circulating VLDLs are hydrolysed by two lipolytic enzymes, lipoprotein lipase and hepatic lipase. Both a decrease in lipoprotein lipase and an increase in hepatic lipase activity have previously been shown to be associated with the accumulation of pro-atherogenic small dense LDL particles, a lipoprotein composition that is particularly evident in the presence of increased VLDL concentrations [17,18]. Consistent with the above, we found an independent association between RPB4 levels and hepatic lipase activity in patients with type 2 diabetes and in those with CAD.…”
Section: Discussionsupporting
confidence: 90%
“…Circulating VLDLs are hydrolysed by two lipolytic enzymes, lipoprotein lipase and hepatic lipase. Both a decrease in lipoprotein lipase and an increase in hepatic lipase activity have previously been shown to be associated with the accumulation of pro-atherogenic small dense LDL particles, a lipoprotein composition that is particularly evident in the presence of increased VLDL concentrations [17,18]. Consistent with the above, we found an independent association between RPB4 levels and hepatic lipase activity in patients with type 2 diabetes and in those with CAD.…”
Section: Discussionsupporting
confidence: 90%
“…38±40 Their origins are unclear, although the lipolytic action of hepatic lipase on LDL enriched in triglycerides due to the activity of lipid transfer protein, has been implicated. 16,41 What remains uncertain is the extent to which these lipoprotein particles may play an active role in the atherogenic process. Numerous studies have demonstrated a negative relationship between obesity and the cholesterol component of HDL.…”
Section: Discussionmentioning
confidence: 99%
“…Higher HL activity increases the conversion of HDL 2 to HDL 3 9,10 and the conversion of large, buoyant LDL to small, dense LDL. 14 The link between IAF and HDL 2 -C metabolism appears to be mediated, at least in part, by hepatic lipase. There is an additional influence of IAF on LDL density beyond the effect of hepatic lipase, perhaps by altering the synthesis of TG-rich lipoproteins.…”
Section: Carr Et Al Regulation Of Hl Activitymentioning
confidence: 99%
“…13 HL also catalyzes the hydrolysis of triglyceride and phospholipid in large, buoyant LDL forming small, dense more atherogenic LDL particles. 14 Increased risk of premature coronary artery disease (CAD) has been shown to be associated with the presence of small, dense LDL particles. [15][16][17][18][19] Similarly, low HDL-C is another major risk factor for CAD.…”
mentioning
confidence: 99%